Effect of protein-energy supplementation in in situ ruminal degradability of NDF and OM of star grass (Cynodon nlemfuensis) in Bubalus bubalis buffalo calves - L?pez, Jos? Ra?l; El?as, Arabel; Delgado, Denia; G?nz?lez, R.; Sarduy, Luc?a; Dom?nguez, Marbelis (Cuban Journal of Agricultural Science, 2011)
Four male buffalo calves (Bubalus bubalis) of the Bufalipso breed with 175 ? 5 kg of liveweight were used and fitted with rumen cannula. A 4 x 4 Latin square design was applied with the object of assessing the effect of the supplementation with different amounts of protein-energy concentrate on the in situ ruminal microbial degradation of NDF and OM of star grass (Cynodon nlemfuensis) forage. Four treatments were used with different amounts of protein-energy supplementation in the diet: 0 (control), 3, 6, and 9 g kg LW-1, given once a day. The ruminal degradation of NDF and OM of the forage showed the highest values (P < 0.05) with rise in the incubation time for the treatments with protein-energy supplementation compared with the control, since 24 h. The supplementation had effect on the rise of the rate of degradation of NDF (0.018, 0.027, 0.029, and 0.030 Fraction h-1) and the decline of the colonization time or ?lag? phase (2.8, 2.2, 2.1, 2.0 h) for the treatments with 0, 3, 6, and 9 g kg LW-1, respectively. However, the rate of OM degradation was higher in the treatments with supplementation (2.8, 2.6, 2.2), for 9, 6, 3 g kg LW-1 with respect to the treatment without supplementation (1.9). The effective degradability was higher in the treatments with supplementation, compared with the control, for NDF and OM in the forage. Multiple regression equations were established to describe the process of degradation of DM, NDF, and OM, in respect to the NDF N-1 consumed in the diet and the time (t) in the rumen. The results proved the positive effect of the supplementation with increasing amounts of concentrate, up to 9 g kg LW-1 in the diet of buffalo calves fed star grass. This could contribute to the increment of the productive activity in buffalo calves under the current rearing conditions. Key words: bufalipso buffalo calves, effective degradability, protein-energy concentrate.